The Effect of Umbilical Cord Milking on Hemodynamic Status of Preterm Infants: A Randomized Controlled Trial. (1st June 2016) - El-Naggar, W; Simpson, D; Hussain, A; Armson, A; Dodds, L; Warren, A; Whyte, R; McMillan, D
Abstract: BACKGROUND: Delayed cord clamping may be difficult to perform in extremely preterm infants. The effects of the alternative, cord milking, have not been fully evaluated. OBJECTIVES: To determine whether cord milking (CM) at birth improves systemic blood flow and short term outcomes, as compared with immediate cord clamping (ICC). DESIGN/METHODS: Babies born to eligible, consenting women presenting in preterm labor between 24 and 31 weeks' gestation were randomized to receive CM or ICC. Echocardiography was performed at 4-6 and 10-12 hours after birth. The primary outcome was systemic blood flow as represented by echo-derived superior vena cava (SVC) flow. Neonatal care staff, echogardiographer and interpreter were blind to the randomization. Analysis was by intention to treat. RESULTS: A total of 73 eligible infants were randomized (37 to CM and 36 to ICC) during the study period (November 2011-2014). There were no statistically significant differences in maternal demographic and antenatal variables. Mean (SD) gestational age was 26.1 (11) weeks and mean (SD) birth weight was 1025 (308) g. 38% of infants were born by vaginal delivery. No significant differences were found between groups in SVC flow, cardiac outputs or neonatal morbidities [table1]. CONCLUSION: There were no statistically significant differences in functional cardiac outcomes, mortality or morbidity between preterm infants who received CM and those who received ICC. Larger trials are needed to establish the best practice in managing the umbilical cord at birth in extremely preterm infants.